IMPLEMENTASI HAL ASASI MANUSIA INTERNASIONAL DALAM PEMENUHAN ASAS MEMBERSHIP OLEH MYANMAR KEPADA ETNIS ROHINGYA - Ayisha Mahadevi; Frisca Arindah; Jastin Mahadana Sandya; Muhammad Fajrin; Nugroho Wisnu (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2022)
The state is obliged to ensure that every citizen gets basic rights, however, in practice the state can fail to fulfill the basic rights of citizens. In Myanmar, cases of human rights violations have occurred for years, namely cases of human rights violations against the Rohingya. Current developments, the Rohingya are still in refugee camps in Bangladesh, because the Myanmar government has not given a sign to accept the Rohingyas back. The research methodology used is qualitative observation with a literature study approach. The observations used in our research use natural setting theory which aims to explore and explore in depth a meaning or problem. During the time the researcher made observations, the research understood and rewrote material related to important and interesting events or phenomena in the context of our group's research. The Rohingya group experienced discrimination from the government and civil society of Myanmar, namely in the form of restrictions on the right to marry and have children, not providing birth certificates, to destroying school buildings as well as mosques and prayer rooms. Myanmar also has the 1982 Citizenship Act to revoke Rohingya citizenship. Myanmar fulfills two important elements in the Internationally Wrongful Act, namely violations of international obligations and these actions can be attributed to Myanmar. The first settlement effort is through the establishment of the International Criminal Court to reconcile human rights violations. Second, efforts to determine the fate of the Rohingya ethnicity in terms of international law, researchers propose that Myanmar provide a membership principle, so that they gain access to education, the economy, and health or the Myanmar government can provide options for the Rohingya ethnic group to continue to join on condition that they are granted special autonomy or grant independence in a voluntary manner. absolute to them.